Study on The Method of Suppressing Cycle Power during Up-shift Process for Wet Dual Clutch Transmission - Qu Siyu; Chen Man; Liu Jikai; Gao Song (Jixie chuandong)
The cycle power,which is prone to appear during shifting process for a wet dual clutch transmission,the life of the clutch is severely affected and the shifting quality is decreased. In response to this phenomenon,the up- shift dynamics equations are derived according to the detailed analysis of up- shifts and the study on the cause of cycle power,during up- shift process of a DCT. Furthermore,the relationship between throttle position,changes in oil pressure and cycle power in the up- shift process is analyzed. The solutions to suppress the cycle power is proposed. A PID method is used to adjust the engine speed by controlling the throttle position. On the basis of disengage clutch and engage clutch,using the fuzzy control theory,taking the driver intention,the deviation of engine speed and target speed as inputs and taking the rise rate of oil- filled pressure as outputs,the up- shift control strategy is designed. It is concluded that the strategy can reduce cycle power effectively and shorten slip energy,jerk. The shifting quality is optimized.